Blockchain applied in healthcare: a bibliometric review - Santos, Barbara Emanuelle Cavalcante dos; Silva, Fernanda Alves da; Araújo, Andressa Clara Barbosa de; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2024)
The healthcare industry has taken advantage of the introduction of digital technologies. The application of Blockchain in healthcare has enormous disruptive potential, as it has the ability to provide greater reliability in the storage of medical records and reduce the risk of tampering. This research aims to present a bibliometric study on Blockchain in health, aiming to identify the main regions in the world that study the subject, the educational institutions that have published the most on the subject and its most recurrent applications. As a methodology, a systematic exploratory procedure was used to extract works from Scopus and Web of Science (WoS) databases, with qualitative analysis facilitated by Microsoft Excel software, where it was possible to analyze the available literature on Blockchain in health. A total of 397 studies out of 967 were selected, being these, 311 articles from Scopus and 86 from WoS. The study revealed that China is the country that has published the most on the subject with 70 articles. In relation to teaching institutions and/or research groups, the IEEE stands out with 8 publications. Finally, Blockchain applications in health, after the standardization carried out, highlight the Medical Data Management with 118 records in the analyzed databases. This bibliometric review shows that there is a lack of studies in Brazil, on the other hand, it shows to be very promising for the health area.
Keywords: Blockchain; Bibliometric Review; health